Técnica PWM baseada em portadora para balanceamento da tensão no capacitor em conversores monofásicos de três níveis com diodo de grampeamento - Bandeira, Marcos Moura (2014)
This paper presents a technique of Pulse Width Modulation (PWM) converters for single-phase three-level with diode clipping, which aims at balancing the tension in the bus capacitors. The technique consists of injecting a signal common mode voltage of the sinusoidal modulating signal width modulation conventional pulse-based Carrier, which introduces an element of DC current in the neutral bus capacitors, this voltage can be controlled, with the main objective to balance the voltage of the capacitor relative to the neutral point. The technique is presented a set of equations, in order to demonstrate how the injected voltage signal introduces a component DC current at the neutral point. To test the proposed strategy, the structure of the three-level converter with diode clipping was simulated with PSIM and mounted using a digital signal processor for generating the control signals of semiconductor devices. Simulations and experimental results that demonstrate the efficiency and quality of the PWM strategy are presented.